Decontamination of Gilson® Pipettes Using High Intensity UV LED (BioTechniques)
Having clean pipettes is a consistent need in any laboratory. Current methods of cleaning, however, are not without downfalls. The process is often time-consuming and utilizes expensive chemicals that can leave residue and eventually cause corrosion. Thus, laboratories are in need of a quick and cost-effective way to decontaminate their pipettes.